Precision technology and sensor applications for livestock farming and companion animals - Kooij, Lenny van Erp - van der, (Brill | Wageningen Academic, 2021)
Are you a student from an animal science or biology background who wants to work with data and technology, or are you from a business, technology or IT background and venturing into the animal sector? This book will guide you into the exciting cross-over field of data science and animal husbandry. After introducing you to the facts and figures of the main animal sectors, you will be inspired by a truckload of sensor applications for animals, from activity collars to rumen boluses, and from facial recognition to virtual fencing. There are not many study books available that contain information on precision technology and animal knowledge, but this book combines these knowledge areas. In separate chapters, the focus is on dairy cows, pigs, poultry, beef and sheep, horses and companion animals, and the sensor applications for these animals. The main trends and concerns in each animal sector are described, as drivers of the technology. Background knowledge on sensors and an introduction to data science techniques with examples of applications in livestock and companion animals make this book a complete and practical guide to the field of precision technology and sensors in the animal sectors."